Respon Siswa Terhadap Penggunaan Facebook Sebagai Media Pembelajaran Matematika (Studi Kasus Terhadap Siswa Kelas X TKJ SMK Muhammadiyah 3 Surakarta Tahun 2015) - Harits, Ma'sum, Masduki, S.Si, M.Si (2015)
This research aims to describe the students' response to the use facebook as a medium of learning Mathematics. This research is a descriptive qualitative research. Data collection techniques with the use of open questionnaire, interview, documentation and observation. Data were analyzed by descriptive methods groove. Validity of the data with triangulation techniques and data sources. Based on the results obtained by students' response to the use of facebook in learning is, joy, enthusiasm, willingness to learn, motivation to learn and student learning effort. It can be seen from the student response indicator, namely (a) there were 73.08% of students expressed delight use facebook, (b) there are 65,4% of students expressed enthusiasm for the use facebook as a medium of learning mathematics, (c) there were 53,85% of students task given through facebook as an indicator of willingness to learn math, (d) there is a positive response to the motivational aspects of learning in terms of students' positive response to the sense of fun, enthusiastic, and a willingness to learn the student, (e) there were 53,85% of students working on task provided through facebook that showed the students' learning efforts. From the results of the study concluded that the use facebook as a medium of learning mathematics to get a positive response from the students.